Respuesta :

rhysr

Answer:

1/2

Step-by-step explanation:

Answer:

x = [tex]\frac{1}{2}[/tex]

Step-by-step explanation:

Given

4x² = 4x - 1 ( Subtract 4x - 1 from both sides )

4x² - 4x + 1 = 0 ← in standard form

To factorise the quadratic

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 4 × 1 = 4 and sum = - 4

The factors are - 2 and - 2

Use these factors to split the middle term

4x² - 2x - 2x + 1 = 0 ( factor the first/second and third/fourth terms )

2x(2x - 1) - 1(2x - 1) = 0 ← factor out (2x - 1) from each term

(2x - 1)(2x - 1) = 0

(2x - 1)² = 0

2x - 1 = 0 ⇒ 2x = 1 ⇒ x = [tex]\frac{1}{2}[/tex] with multiplicity 2